Educational Status of Mothers: Implication for Preschoolers' Nutritional Intake in Ibadan Metropolis, Nigeria (2012)
"The study was carried out to assess the impact of the educational status of mothers on preschooler's nutritional intake. The children in Ibadan Metropolis were used as a case study. Simple statistical anaiysis was employed to explain the socio economic characteristics of the mothers. The daily dietary intake of the children was recorded and weighed against the recommended dietary allowance given by the FAO/WHO. The results showed that as the calorie intake increases, the protein also increases, sharing a positive relationship. Results also revealed that mothers with no formal education had children with the highest level of intake in both calorie and protein. The mothers with secondary school education were found to give the least to their children which will indeed be associated with the nature of their jobs. Male children were shown to consume more than the female children. On the average, 72.08% of the recommended for calorie was met and 96. 8% for the protein was met. Regression results showed that protein intake and class of the child is positively related to the level of calorie intake. The age of the child and educational status of the mother was shown to be negatively related to the level of caloric intake. It was therefore recommended that programmes on the nutritional needs of a child by the Government while mothers be encouraged to have vegetable gardens behind their houses, making it cheaper and more easily accessible. This will certainly improve the daily intakes and the nutritional status of children "